The positive role of religiosity in dealing with academic dishonesty - Ridwan Ridwan; Yossi Diantimala (Cogent Business & Management, 2021)
This study examines the role of religious knowledge and activity in dealing with academic dishonesty. Furthermore, we investigate whether the locus of control and personality strengthen the relationship between religious knowledge and activity and academic dishonesty. The study investigates 235 respondents from accounting and medical undergraduate students of Syiah Kuala University, the largest university in Aceh Province, Indonesia. They are prospective accountants, auditors, and doctors. The sample is determined by using a random sampling technique, where all students have the opportunity to fill out the online questionnaire provided through Google form. The questionnaire can be accessed in 2 months, June-August 2019. Respondents are directed to answer 97 questions divided into five specific sections of the variables. Respondents must complete each section before going to the next section and unable to change the previous section's answers. To test the hypothesis, we employ path analysis. The results show that religious knowledge is the main predictor in dealing with academic dishonesty and the basis for building the character of the students. Locus of control strengthens the effect of religious knowledge on academic dishonesty, but personality does not. Religious knowledge and activity should be synergized in the higher education system and must be well arranged and structured to function well in preparing honest accountants, auditors, and doctors.
Keywords: 650; academic dishonesty; locus of control; personality; religious knowledge; religious activity; university